Polio: The road to eradication threatened - Choudhary Ahmed Hasan; Areeba Ahmed; Fariha Hasan (Journal of the Pakistan Medical Association, 2020)
Madam, Despite being eradicated all over the world, Pakistan is one of the few countries still struggling to defeat the paralyzing enemy – polio [1]. As Coronavirus Disease 2019 (COVID-19) exposed the already struggling health care system in Pakistan, the Global Polio Eradication Initiative announced to suspend all polio vaccination programs, to stop the spread of COVID-19 [2]. The suspension of mass-immunization campaigns has led to an upsurge in the polio cases, with 50 cases already reported in Pakistan so far [3]. Even though Pakistan was on the brink of becoming polio-free in 2017, with only a total of 8 cases reported, the anti-vaccination propaganda and lack of proper measures by the government the country saw a massive upsurge in polio cases in 2019 with the total number of cases being 147 [3]. As our healthcare sector has already been stretched thin with COVID-19 cases, the threat of another pandemic is the last thing the country needs. Pakistan is destined to see the birth of 5 million children in the next 9 months following recognition of COVID-19 as a pandemic in March 2020 [4]. Thus, if the state does not take any step to heighten further the measures of preventing this likely emergency, hundreds and thousands of children may be at risk of getting infected with the crippling poliovirus. The spread of polio has been declared as an international public health concern [5]. The currently suspended immunization campaigns only add to the insult, which could cause an uprise in cases in those countries which have already been declared polio-free and can lead to travel restrictions for travel to and from Pakistan. With a weak healthcare system, and low budget, showing that the government spends just 1% of GDP on each person’s healthcare, it is unlikely for the country to be well-equipped to tackle this huge burden of polio cases whilst struggling to deal with COVID-19 [6]. Continuous...